Investigation of local stimulation effects of embedding PGLA at Zusanli (ST36) acupoint in rats based on TRPV2 and TRPV4 ion channels - Hou, Xunrui; Liang, Xin; Lu, Yuwei; Zhang, Qian; Wang, Yujia; Xu, Ming; Luo, Yuheng; Fan, Tongtao; Zhang, Yiyi; Ye, Tingting; Zhou, Kean; Shi, Jiahui; et al. (Frontiers in Neuroscience, 2024)
IntroductionAcupoint Catgut Embedding (ACE) is an extended and developed form of traditional acupuncture that serves as a composite stimulation therapy for various diseases. However, its local stimulation effects on acupoints remain unclear. Acupuncture can activate mechanically sensitive calcium ion channels, TRPV2 and TRPV4, located on various cell membranes, promoting Ca2+ influx in acupoint tissues to exert effects. Whether ACE can form mechanical physical stimulation to regulate these channels and the related linkage effect requires validation.MethodsThis study investigates the influence of TRPV2 and TRPV4 ion channels on the local stimulation effects of ACE by embedding PGLA suture at the Zusanli (ST36) acupoint in rats and using TRPV2 and TRPV4 inhibitors. Flow cytometry, immunofluorescence, Western blot, and Real-time quantitative PCR were employed to detect intracellular Ca2+ fluorescence intensity, the expression of macrophage (Mac) CD68 and mast cell (MC) tryptase, as well as the protein and mRNA expression of TRPV2 and TRPV4 in acupoint tissues after PGLA embedding.ResultsThe results indicate that ACE using PGLA suture significantly increases the mRNA and protein expression of TRPV2 and TRPV4, Ca2+ fluorescence intensity, and the expression of Mac CD68 and MC tryptase in acupoint tissues, with these effects diminishing over time. The increasing trends are reduced after using inhibitors, particularly when both inhibitors are used simultaneously. Furthermore, correlation analysis shows that embedding PGLA suture at the ST36 acupoint regulates Mac and MC functions through Ca2+ signaling involving not only TRPV2 and TRPV4 but multiple pathways.DiscussionThese results suggest that embedding PGLA suture at the ST36 acupoint generates mechanical physical stimulation and regulates TRPV2 and TRPV4 ion channels, which couple with Ca2+ signaling to form a linkage effect that gradually weakens over time. This provides new reference data for further studies on the stimulation effects and clinical promotion of ACE.